Analisis Kelimpahan dan Pola Pertumbuhan Kepiting Bakau di Sungai Selindung, Kota Pangkal Pinang, Kepulauan Bangka Belitung - Christin Claudia Tambunan; Okto Supratman; Kurniawan Salim; Okto Supratman (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Mud crab is one of the important fishery commodities in Indonesia since the 1980s. Mud crabs have high economic value and are closely related to the mangrove ecosystem area so many people want to hunt them for sale. This study is conducted to determine the abundance and growth patterns of mud crabs in the Selindung River, Pangkalpinang, Bangka Belitung Islands. Sampling is carried out from February to March 2023 at Selindung river using folding traps. Mud crab sampling is carried out every 2 weeks starting from the lowering of the trap at 18.00 WIB until the removal of the trap at 07.00 WIB. The mangrove crabs found were counted for the number of individuals, measured for carapace width, body weight and sex, then analyzed. Measurement of physico-chemical parameters of waters including temperature, pH, salinity, dissolved oxygen (DO). The results of the study concluded that there were 2 types of mangrove crabs found in the Selindung River, Pangkalpinang City, namely the type of S. serrata and the type of S. tranquebarica. The abundance of mangrove crabs in the Selindung River, Pangkalpinang, Bangka Belitung Islands, is the highest for the type S. tranquebarica of 82.97%. The growth pattern of mud crabs in Selindung River, Pangkalpinang City, Bangka Belitung Islands is negative allometric. The condition factor of mangrove crabs at each station morphologically has a fit body condition. Parameters that have a positive correlation with the abundance of mud crabs are pH, DO, and substrate.